2019
DOI: 10.1155/2019/6154867
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Anti-Biofilm Effect of an Electrolyzed Superoxidized Solution at Neutral-pH againstHelicobacter pylori

Abstract: The presence of Helicobacter pylori in the oral cavity has been associated to the failure of antimicrobial therapy in patients with gastrointestinal infection and the development of oral diseases. However, it has been reported that the maintenance of good oral hygiene can improve the therapeutic success rates, where the use of mouthwashes with anti-Helicobacter activity would help to achieve it. The aim was to evaluate the antimicrobial activity of OxOral® mouthwash against H. pylori and its effect on biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Electrolyzed water is obtained from the combination of tap water with a sodium chloride-derived solution passed through an electrolysis chamber, and it has been proven to be a cheap and environment-friendly alternative to disinfect different types of contaminated surfaces and inert materials due to its vast microbicide properties [53].…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyzed water is obtained from the combination of tap water with a sodium chloride-derived solution passed through an electrolysis chamber, and it has been proven to be a cheap and environment-friendly alternative to disinfect different types of contaminated surfaces and inert materials due to its vast microbicide properties [53].…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyzed water is obtained from the combination of tap water with a sodium chloride-derived solution passed through an electrolysis chamber, and it has been proven to be a cheap and environment-friendly alternative to disinfect different types of contaminated surfaces and inert materials due to its vast microbicide properties [53]. In the present revision, the included studies assessed several types of differently obtained electrolyzed waters, which showed a high disinfection potential when used to deal with different oral conditions, including caries, periodontal disease, and root canal system infection.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that Estericide Qx® provides a broad-spectrum antibacterial activity mainly in Gram-negative [ 44 ]. Other studies, Lucio-Sauceda et al, reported a significant anti- H. pylori activity of OxOral® by microdilution assays, and Rivera-Garcia et al observed a significant antimicrobial activity against Listeria monocytogenes on eggshells [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cations are drawn towards the electrode negative, where they receive electrons, forming a negatively charged antioxidant solution (alkaline solution). At the positive electrode, anions are attracted, which give up their additional electrons to create a positively charged oxidant solution (acid solution) [ 18 ]. For ESS formation, part of an antioxidant solution formed is channeled back into the anode chamber, thus increasing the content of hypochlorite ions (OCl − ).The reintroduction of the alkaline solution back into the acidic solution allows adjusting the pH up to neutral.…”
Section: Introductionmentioning
confidence: 99%